Comparison Between Tai Chi and Balance Training on Spatiotemporal Parameters and Dual‐Task Costs During Stair Negotiation in Participants With Knee Osteoarthritis: A Randomized Controlled Trial. - Zhang, Hanjing; Zheng, Jiaqi; Chai, Yatai; Huang, Xiaofei; Wang, Xiangbin; Hou, Meijin (Physiotherapy Research International, 2025)
Background and Purpose: To compare the effects of Tai Chi and balance and postural control training on spatiotemporal parameters and dual‐task costs during stair negotiation in knee osteoarthritis participants. Methods: Sixty‐nine knee osteoarthritis participants were randomly assigned to either the Tai Chi group or the balance and postural control training group. All participants underwent interventions twice a week for 12 weeks. Pain scores, spatiotemporal parameters and dual‐task costs during stair ascent and descent were measured before and after the intervention. Results: Both groups reported significant reductions in pain and improvements in spatiotemporal parameters following the intervention. The Tai Chi group exhibited a significantly greater reduction in initial double stance time during stair descent compared with the balance and posture control training group under both single‐task (F = 8.177, p = 0.006, η2 = 0.143) and dual‐task (F = 5.007, p = 0.03, η2 = 0.093) conditions. Meanwhile, the balance and posture control training group showed significant reductions in the dual‐task cost values of cadence (p = 0.003) and speed (p = 0.038), although no significant between‐group differences were observed. Discussion: Both Tai Chi and balance and postural control training alleviated pain and improved spatiotemporal parameters during stair negotiation in participants with knee osteoarthritis. However, improvements in dual‐task cost of cadence and speed were limited, potentially due to insufficient intervention or gait strategy adaptations. Only the balance and postural control group showed a significant reduction in dual‐task cost during stair descent, indicating its advantage in maintaining stability under cognitive load. Trial Registration: ChiCTR1800018028